2013
DOI: 10.1002/chem.201301787
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Sulfide Ligands for Allylic CH Oxidations of Terminal Olefins

Abstract: Perfect to a THT! Screening a diverse library of thioether ligands led to the discovery of tetrahydrothiophene (THT) as a highly reactive and selective ligand for Pd-catalyzed allylic CH oxidation reactions. This novel ligand system provides some of the highest reported yields for the formation of (E)-linear allylic acetates through allylic CH activation chemistry (BQ = 1,4-benzoquinone).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The simple and inexpensive method was used for the synthesis of tetrahydrothiophenes which was highly active and linear-selective ligand using palladium-sulfide as catalyst (Figure 7, method b). [36] The palladium-sulfide catalytic system was developed to achieve aerobic turnover with 4,5-diazafluorenone ligand (Figure 7, method c). This system proved to be highly selective for linear allylic acetates with good yields and functional group tolerance [37].…”
Section: Palladium-catalyzed Direct Oxidation Of Alkenes With Molecular Oxygenmentioning
confidence: 99%
“…The simple and inexpensive method was used for the synthesis of tetrahydrothiophenes which was highly active and linear-selective ligand using palladium-sulfide as catalyst (Figure 7, method b). [36] The palladium-sulfide catalytic system was developed to achieve aerobic turnover with 4,5-diazafluorenone ligand (Figure 7, method c). This system proved to be highly selective for linear allylic acetates with good yields and functional group tolerance [37].…”
Section: Palladium-catalyzed Direct Oxidation Of Alkenes With Molecular Oxygenmentioning
confidence: 99%
“…[43] Scheme 25. A set of mechanistically oriented experiments led the authors to rule out a branchedto-linear equilibration of the allylic acetate product, as well as the involvement of an η 3 -allyl palladium intermediate.…”
Section: Acetoxylations Hydroxylationsmentioning
confidence: 99%
“…In a more comprehensive survey of palladium-sulfide catalysts, Stambuli later demonstrated that the simple and inexpensive tetrahydrothiophene was a highly active and linear-selective ligand (Scheme 15, b). 25 In an effort to move away from the use of stoichiometric quantities of oxidants such as p-benzoquinone or copper additives, Stahl developed the first catalytic system to achieve aerobic turnover with 4,5diazafluorenone ligand 24 (Scheme 15, c). 26 This system proved to be highly selective for linear allylic acetates with good yields and functional group tolerance.…”
Section: Scheme 14 Tetracyclic Flavonoid Synthesis By Intramolecular mentioning
confidence: 99%